2018
DOI: 10.4018/978-1-5225-3949-0.ch017
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Assisted-Learning Approach in Enhancing the Student Teacher's Vocabulary and Usage of Mobile Phone

Abstract: Mobile learning facilitates delivery of learning using portable electronic devices. This study investigated the effectiveness of mobile assisted learning in the development of vocabulary and usage of mobile phone. Specifically, the primary objectives of the study were to compare the effectiveness of Mobile Assisted Learning Approach and Conventional Learning Approach with reference to Vocabulary and Usage of Mobile Phone and also to analyze the interaction between treatments with gender and subject background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…By utilising language learning technology, instructors can assist students in becoming better equipped for action (Boix Mansilla & Jackson, 2011). Mobile devices offer a wide variety of language learning applications and have a substantial impact on college students' vocabulary and grammar understanding (Alkhezzi, 2016;Dange, 2018). One Chinese institution found that WeChat, a well-known social media platform, was very helpful in teaching students English as a second language (Shi et al, 2017).…”
Section: Promising Teaching Practisesmentioning
confidence: 99%
“…By utilising language learning technology, instructors can assist students in becoming better equipped for action (Boix Mansilla & Jackson, 2011). Mobile devices offer a wide variety of language learning applications and have a substantial impact on college students' vocabulary and grammar understanding (Alkhezzi, 2016;Dange, 2018). One Chinese institution found that WeChat, a well-known social media platform, was very helpful in teaching students English as a second language (Shi et al, 2017).…”
Section: Promising Teaching Practisesmentioning
confidence: 99%
“…Instructors can help students become more prepared to take action by making use of technologies that facilitate language learning (Boix Mansilla & Jackson, 2011). Mobile devices supply numerous language learning applications and significantly impact college students in areas such as comprehension of vocabulary and grammar (Alkhezzi, 2016;Dange, 2018). One university in China found the popular social media WeChat to be highly effective at helping students learn English as a second language (Shi, Luo, & He, 2017).…”
Section: Language Learningmentioning
confidence: 99%